Sparkol Videoscribe Usage on Colloid Material as a Media for Chemistry Education - Reni Septiani; Supriadi Supriadi; Ijirana Ijirana (Jurnal Akademika Kimia, 2020)
This research method was research and development (R & D), which purposed to obtain the sparkol videoscribe designs of colloidal material and the validity of designs that were reviewed by experts as theoretical experts. The object of this study was sparkol videoscribe. Data collection was divided into two, namely media design data and media validity that were designed by using assessment sheets from 5 experts, 3 people were the learning media experts and 2 people were the chemical material experts. Data were analyzed descriptively to determine the justification of the validity of the research object. The results of the data analysis obtained that sparkol videoscribe design of material colloid had characteristics, namely images, moving hand animation, music, explanation of material in the form of sound and the composition of sentences incorporated in whiteboard animation. The designs were declared valid with a very good category according to experts and can be used as a chemistry education media with a score of 3.7 based on the total score of the instructional media experts and 3.45 based on the total score of the chemical material experts.